The Impact of Brand Image on Purchasing Decisions on 3 Second Brand Products - Nugroho, Dwi Agus; Fadhilah, Muinah; Cahya, Agus Dwi (Jurnal Ekonomi dan Bisnis, 2024)
This study aims to determine whether product design and content marketing variables affect purchasing decisions on products from 3Second brands with brand image as an intervening variable. This study took samples from consumers who were in the Special Region of Yogyakarta. The sampling method is non-probability, and the sampling technique uses purposive sampling. Data collection was done through a messenger with questionnaires sent via Whatsapp. The number of respondents processed was 105 respondents and the data was analyzed using SPSS. The results showed that the variables of product design, content marketing and brand image had a positive and significant effect on purchasing decisions. The results also showed that product design and content marketing variables had a positive and significant effect on brand image. Product design variables mediated by brand image have a positive and significant influence on purchasing decisions. Content marketing variables mediated by brand image have a positive and significant influence on purchasing decisions.